Efektivitas Simulasi Pola LED Menggunakan Tinkercad: Media Pembelajaran Inovatif pada Elektronika Dasar - Riskawati; Said, Sukmawati; Herman, Nurul Mutmainnah (Universitas Pendidikan Ganesha, 2024)
The use of simulation-based learning media has emerged as an innovative solution to address the limitations of physical facilities in basic electronics education. This study aims to evaluate the effectiveness of LED pattern simulations using Tinkercad as an interactive learning medium in improving students' understanding of basic electronics concepts. This research employed a pre-experimental approach involving 60 students enrolled in a Basic Physics course. Students were guided to design and test LED patterns using Tinkercad, followed by evaluations through understanding tests and questionnaires. The results indicated a significant improvement in students' average understanding scores, from 65 before the simulation to 75 after. Additionally, the majority of students (78%) found the simulation engaging and helpful in simplifying the learning process. Tinkercad simulations proved to provide instant feedback, support student exploration, and enable interactive self-directed learning. This study concludes that Tinkercad is effective as an innovative learning medium for teaching electronics circuit concepts and can serve as a relevant alternative in formal education and remote learning environments.